Analisis Penerapan Just In Time (JIT) dalam Meningkatkan Efisiensi Persediaan dan Biaya Operasional Perusahaan: Sebuah Literature Review - Siti Nur Reskiyawati Said (Journal of Literature Review, 2026)
Just In Time (JIT) is an inventory management and production system that aims to provide materials and products precisely according to production needs and customer demand. This study aims to analyze the implementation of the Just In Time method in improving inventory efficiency and reducing operational costs through a literature review approach. The method used is a qualitative literature review by examining various scientific articles discussing the application of JIT in manufacturing and service companies. The findings indicate that JIT contributes significantly to reducing inventory holding costs, optimizing warehouse utilization, improving inventory turnover, and enhancing production efficiency. In addition, JIT supports better cash flow management by minimizing capital tied up in inventory. However, successful implementation depends on supplier reliability, integrated information systems, production planning accuracy, and organizational readiness. Several studies also reveal that JIT implementation can increase responsiveness to market demand and improve product quality through continuous process improvements. Nevertheless, companies may face challenges such as supply chain disruptions, demand uncertainty, and high dependence on suppliers. Therefore, organizations need comprehensive planning and strong coordination to maximize the benefits of JIT implementation. Overall, JIT is an effective strategy for achieving inventory efficiency and operational excellence in a competitive business environment.